HUBUNGAN PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN JUMLAH GIGI YANG BERFUNGSI PADA LANJUT USIA DI PANTI PELAYANAN LANJUT USIA WANA SERAYA BIAUNG DENPASAR - Ni Wayan Yuditami; Ni Wayan Arini; I Nyoman Wirata (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Aging is a process that can not be avoided by any human being, where there is a change in the process is a very complex body tissues as well as in the oral tissues. Knowledge is an impression in the minds of human as a result of the use of the five senses. Dental and oral health maintenance is to maintain oral hygiene from food residue and other debris in the mouth, with the aim to keep teeth healthy. Referring to the results of the survey in Hong Kong, the Asian countries with similar socio-cultural and Indonesia obtained for 12% of the elderly are not toothed and still have an average of 15 teeth to function. This study aims to gain an relation of knowledge about oral health care and the number of teeth that function in the elderly in the Home Care Elderly Wana Seraya Biaung Denpasar in 2013. This research is a descriptive study by using the total population. The study of 42 elderly suggests elderly who are knowledgeable about oral health care found that most of the elderly in the Home Care Elderly Wana Seraya Biaung Denpasar have less knowledge of the criteria are as many as 21 people with percentage 50 %, The average teeth of function in the elderly is as much as seven and average teeth of function based on the level of knowledge of dental and oral health maintenance by good criteria was 18.12. Knowledge level of elderly is positively connected with the amount teeth of function on elderly as big as 0,351 (r=0,351) with relation power as big as p=0,023 ( p-value 0,05 ).